Dupilumab Demonstrates Rapid Onset of Response Across Three Type 2 Inflammatory Diseases - Giorgio Walter Canonica; Arnaud Bourdin; Anju T. Peters; Martin Desrosiers; Claus Bachert; Stephan Weidinger; Eric L. Simpson; Nadia Daizadeh; Zhen Chen; Siddhesh Kamat; Asif Khan; Jingdong Chao; et al. (2022)
Type 2 inflammatory diseases often coexist in patients. Dupilumab targets type 2 inflammation and has demonstrated treatment benefits in patients with atopic dermatitis (AD), asthma, and chronic rhinosinusitis with nasal polyps (CRSwNP) with an acceptable safety profile.This post hoc analysis across five phase 3 studies in patients with moderate to severe AD or asthma, or severe CRSwNP, evaluated time of onset and duration of the treatment response.Patients received subcutaneous dupilumab 200/300 mg or placebo. Assessments included the Eczema Area and Severity Index, Peak Pruritus Numerical Rating Scale, and Dermatology Life Quality Index in AD; pre-bronchodilator FEV1, daily morning peak expiratory flow, and symptom scores in asthma; and University of Pennsylvania Smell Identification Test, daily nasal congestion, and loss of smell scores in CRSwNP.At week 2 after the initiation of dupilumab versus placebo, 67.8% versus 36.5% of AD patients achieved a clinically meaningful benefit (Eczema Area and Severity Index: 50% or greater improvement; Peak Pruritus Numerical Rating Scale: 3 point or greater improvement; or Dermatology Life Quality Index: 4 point or greater improvement) (P < .001). Moreover, 61.6% versus 39.9% of asthma patients achieved improvements in pre-bronchodilator FEV1 of 100 mL or greater and 48.8% versus 26.3% achieved 200 mL or greater improvement (both P < .001); 33.2% versus 5.6% of CRSwNP patients regained a sense of smell (P < .001). Treatment effects further improved or were sustained to the end of treatment.Clinically meaningful responses were achieved rapidly after the first dupilumab dose in AD, asthma, or CRSwNP and were sustained throughout treatment (see Video in this article's Online Repository at www.jaci-inpractice.org).